CORRELATION OF PRESSURE STIMULATED CURRENTS IN ROCKS WITH THE DAMAGE PARAMETER - Anastasiadis C.; Stavrakas I.; Triantis D.; Vallianatos F. (My University, 2007)
Presure Stimulated Current (PSC) experiments were conducted on marble samples to correlate PSC with the damage parameter, D. The phenomena and procedures taking place in the vicinity of the fracture limit were observed and analytically described. PSC recordings were conducted by application of uniaxial compressional stress, both at a constant stress rate and at a constant deformation rate. A linear relationship was shown to exist between the emitted PSC and the damage parameter which quantifies the deviation from linear elasticity and the concentration of microcracks.
Keywords: DAMAGE PARAMETER; FRACTURE; PRESSURE STIMULATED CURRENT (PSC)